PENGARUH KOMUNIKASI, MOTIVASI INTRINSIK DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DI PT JOVAN TECHNOLOGIES - Metta, Tri; Saputra, Asron (LPPM Universitas Putera Batam, 2021)
Companies that have determined their goals will definitely try to achieve the goals they have determined. In achieving its goals, company doesn’t only depend on technological excellence, operating funds, existing facilities and infrastructure, but the company also depends on aspects of its resources owned by the company. This research is to test and analyze the Problems of Communication, Intrinsic Motivation and Job Training on Employee Performance at PT Jovan Technologies. The technique used in this study is a saturated sample or census with a total of 113 respondents. The measuring instrument used was 5 point likert scale. The analytical method used is multiple linear regression with the help of spss 22 statistical software. Based on the results of the study, showed that Communication, Intrinsic Motivation and Job Training had a positive and significant effect on employee performance from t calculate > t table and significant value <0.05 and Communication, Intrinsic Motivation and Job Training together have a positive and significant effect on employee performance from f calculate > f table and significant value <0.05.